New Techniques for Determining the Longitudinal Effects of Local Hemodynamics on the Intima‐Media Thickness in Arteriovenous Fistulae in an Animal Model. Issue 4 (22nd November 2013) - Rajabi‐Jagahrgh, Ehsan; Roy‐Chaudhury, Prabir; Wang, Yang; Al‐Rjoub, Marwan; Campos‐Naciff, Begona; Choe, Ann; Dumoulin, Charles; Banerjee, Rupak K.
Abstract Remodeling in the arteriovenous fistulas (AVFs) is believed to be a hemodynamic‐driven process, which results in extreme changes in the diameter and intima‐media thickening (IMT) of vessels over time. This study aims to describe the successful development of techniques that enabled correlation of changes in local and longitudinal wall shear stress (WSS) with the temporal variations of the diameter and IMT in the venous segment of AVFs. An AVF was created between the femoral artery and vein of a 50‐kg pig. We have previously shown the successful use of CT‐scan and ultrasound techniques for anatomical and flow measurements in AVFs, respectively. In this study, we developed new techniques involving markers (both in vivo and ex vivo), casting (ex vivo), and micro‐MRI (ex vivo; 7 Tesla). A radiopaque marker (ROM) was sutured to the AVF at the day of surgery, which was visible in the CT‐scan images, micro‐MRI, and histology sections. Therefore, ROM served as a fixed local reference for both in vivo and ex vivo states of AVFs. Immediately after sacrificing the pig, a procedure was developed to create a cast from the AVF and thus, maintaining the in vivo state of the AVF during the histology process. Then, micro‐MRI and histology techniques were conducted on the AVF to measure IMT in the vein. Along the ROM, the local changes in WSS levels for two cross‐sections were tracked at 2D (D: days) and 28D post surgery. WSS levels reduced from 2D to 28D for both cross‐sections. Also, the recirculation zones, which formed at 2D for both sections, became smaller in size at 28D. These hemodynamic changes were then mapped onto the corresponding IMT measurements from histology and micro‐MRI. It was observed that the recirculation zones at 2D and 28D corresponded to the largest IMT in the two sections. In summary, the new methodologies allowed us to define a fixed local reference at all time points in the AVF, which enabled accurate tracking of local changes in hemodynamics (WSS), configuration (diameter), and structure (IMT) of the venous segment over time. This also empowered study of the interactions between these parameters, which could improve our understanding about the hemodynamic‐driven remodeling in AVFs. From a clinical point of view, this information could be translated into local and early therapeutic interventions for dialysis patients.